Gray Matter Volume of the Lingual Gyrus Mediates the Relationship between Inhibition Function and Divergent Thinking - Zhang, Lijie; Qiao, Lei; Chen, Qunlin; Yang, Wenjing; Xu, Mengsi; Yao, Xiaonan; Qiu, Jiang; Yang, Dong (Frontiers in Psychology, 2016)
Abstract: Although previous research provides converging evidence for the role of posterior regions of the brain (including temporal, occipital, and parietal regions) involved in inhibition on creative thinking, it remains unclear as to how these regions influence individual differences in creative thinking. Thus, we explored the relationship between posterior regions (i.e., hippocampal, parahippocampal, lingual gyrus, precuneus, and cuneus) , inhibition function, and divergent thinking in 128 healthy college students. The results revealed that lower inhibition was associated with larger gray matter volume (GMV) in the lingual gyrus, which in turn was associated with higher divergent thinking. In addition, GMV in the lingual gyrus mediated the association between inhibition and divergent thinking. These results provide new evidence for the role of inhibition in creative thinking. Inhibition may affect the amount of information stored in long-term memory, which, in turn influences divergent thinking.